Pengaruh Asimetri Informasi Pada Senjangan Anggaran dengan Kejelasan Sasaran Anggaran dan Komitmen Organisasi Sebagai Pemoderasi - Ayuni, Ni Made Kusuma; Erawati, Ni Made Adi (E-Jurnal Akuntansi, 2018)
Budget is a future financial plan that covers management's expectations of revenue, expenses and other financial transactions within a year. The budget of a public organization includes plans on how much the plan will cost and how much money and how to fund money to realize the plan. Budgetary slack is a gap by managers or subordinates in participating to budget by giving budget estimates that do not fit the actual situation. This study aims to determine the effect of information asymmetry on budgetary slack, with clarity of budget target and organizational commitment as a moderating variable. This research was conducted at the regional device work unit of departement in Tabanan Regency. The population in this study are 19 departement and the number of samples studied were 57 people. The technique of determining the sample used in this study is saturated samples method that all the population can be used as research samples. Respondent of sample in this research is head of department, head of sub. general and planning section, and head of sub. financial department. Data collection was done through questionnaires. Data analysis techniques used are simple linear regression analysis and moderated regression analysis. Based on the results it is concluded that the information asymmetry has a positive effect on budgetary slack, the clarity of the budget target has negative effect (weakening) the relationship of information asymmetry on budgetary slack, and organizational commitment does not moderate the relationship of information asymmetry at budgetary slack of Tabanan District Government. Keywords: information asymmetry, budgetary slack, clarity of budget target, organizational commitment.